E. J. Lowe on the modal ontological argument - Eklund, Dan-Johan (Religious studies, 2020)
E. J. Lowe has defended a modal ontological argument that draws upon Plantinga's version. Briefly, the argument is this: God is a necessary being; possibly, God exists; hence, God exists. In this article, I accept the validity of Lowe's modal ontological argument and focus on how he seeks to justify the argument's possibility claim in reference to his essence-based account of modal knowledge. I argue that here Lowe's defence fails. I have two complaints. I call them 'the modified "perfect island" objection' and "the conflicting possibilities objection". Both of these refer to the concern that Lowe's modal epistemology is too permissive: it permits justification of possibility claims that question the acceptability of the underlying modal epistemology.